Implementation of a no Smoking Area at SMPN 12 Malang in the Janti Health Center Working Area - Emil Nahdiyah; Sri Winarni; Ganif Djuwadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Smoking is harmful to our health and the health of those around us. Diseases caused by smoking can ultimately weaken the potential of human resources. In response to this, the government has established a program to deal with cigarette smoke, one of which is a smoke-free area, and there are seven places that must implement a smoke-free area, one of which is a place of teaching and learning. Objective: The purpose of this study was to determine the implementation of a smoke-free area at SMPN 12 Malang in the working area of the Janti health center as a step towards realizing a smoke-free school environment. Method: This research uses quantitative methods that are descriptive in nature. The population of this study is the whole of the research object. The sampling technique used was total sampling totaling 72 people. The sample in this study were all teachers, staff, security officers, janitors, and canteen guards at SMPN 12 Malang. Data collection techniques are questionnaires, observations, and interviews, the instruments used are questionnaire sheets, observation sheets, and interview guidelines. Result: The results of research on the implementation of a smoke-free area at SMPN 12 Malang found that the policy pattern is good because it already has a policy, human resources are sufficient because there is no special officer to supervise the smoke-free area and sanctions for violators of the smoke-free area, and the area sign in the good category has been installed but the placement is still not strategic because it is installed in front of the class and covered by lush trees, and the media used is only one, namely the statue of the no-smoking area sign or smoking ban. Conclusion: The implementation of a smoke-free area at SMPN 12 Malang in the policy pattern is in the good category, human resources are sufficient, and the smoke-free area sign is good.